DAYA TAWAR WARISAN BUDAYA KOTA LAMA SEMARANG SEBAGAI DAYA TARIK WISATA MELALUI PROGRAM REVITALISASI - Apit Buchori (Kepariwisataan: Jurnal Ilmiah, 2022)
The writing and discussion that researchers are currently doing is presenting the history of the formation and development of the Semarang Old City area since the Dutch colonial era and the revitalization efforts carried out by the Semarang city government as a cultural and tourism wealth of Semarang City. The Old City of Semarang is recognized as a cultural heritage that has a long historical value where this area was built at the end of the 17th century after an agreement was signed between the VOC and the Islamic Mataram kingdom in which the contents of the agreement the Islamic Mataram kingdom would hand over Semarang if the VOC succeeded in conquering the rebellion led by Trunojoyo. Since then, after the handover the VOC built various buildings in the Old City which at that time served as the center of government, industry and trade. Since then, the Old City of Semarang has been dubbed the Little Netherland, considering the atmosphere of the city and the buildings that have been built have similar views to cities in the Netherlands. The large number of historical buildings in European style with unique shapes supported by a well-organized urban spatial arrangement is a special charm for the community, including tourists who visit the city of Semarang. Based on this potential, finally in 2012 the Semarang city government took the decision to start reviving and rebuilding the Old City of Semarang to serve as a leading tourist destination.Keywords: Old Town History, Tourist Attraction, Cultural Heritage, Revitalization